1986
DOI: 10.1007/bf00256700
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial of folinic acid to reduce vincristine neurotoxicity

Abstract: In a murine model system, folinic acid demonstrated host-protective properties during administration of repetitive and lethal doses of vincristine (VCR). Subsequently, folinic acid was evaluated in patients receiving VCR during an adjuvant chemotherapy program for stage II carcinoma of the breast. The toxicities, cumulative VCR dosage, and percentage of ideal dosage observed in 18 patients receiving folinic acid have been compared with those observed in 70 patients who previously received VCR without folinic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Folinic acid and pyridoxine have been tried as possible antidotes but gave no protection. 15,16 Recently, oral glutamic acid therapy has been tested, with encouraging results. 17 Results from animal experiments and human observations show that the administration of lithium may counteract vincristineinduced neurotoxic effects.…”
Section: Commentmentioning
confidence: 99%
“…Folinic acid and pyridoxine have been tried as possible antidotes but gave no protection. 15,16 Recently, oral glutamic acid therapy has been tested, with encouraging results. 17 Results from animal experiments and human observations show that the administration of lithium may counteract vincristineinduced neurotoxic effects.…”
Section: Commentmentioning
confidence: 99%
“…Glutamic acid, ORG-2766 (an adrenocorticotrophic hormone analogue) and noscapine have also been stated to protect against vincristine-induced neuropathy. Folinic acid has also been used successfully in a small number of vincristine overdosages in humans 13 15 16…”
Section: Discussionmentioning
confidence: 99%
“…The earliest and most prominent symptom of peripheral neuropathy is loss of the Achilles tendon reflexes. 6,7 The higher the dose of the drug and the longer the treatment period, the more severe the drugrelated neurotoxicity. In one study, sensory neuropathy was found in one third of patients 77 months after cessation of therapy.…”
Section: Discussionmentioning
confidence: 99%